Efektivitas Konseling Kelompok dengan Pendekatan Rational Emotive Behavior Therapy untuk Meningkatkan Self Awareness - Nabillah Adhistia; Kusnadi Kusnadi; Lena Marianti (Journal of Society Counseling, 2023)
This research is entitled "The effectiveness of group counseling using the Rational Emotive Behavior Therapy approach to increase Andikpas' Self Awareness". The aim of this research is to describe the level of self-awareness of andikpas, as well as help andikpas with low self-awareness. This research used a true experimental method with a population of 113 people and a sample of 32 respondents. Sampling used a purposive sampling technique, with a total of 24 respondents, data collection techniques used questionnaires and documentation. The data analysis technique uses a paired sample t-test with the help of SPSS 23. The results of the research show that the level of self-awareness andikpas is in the medium category at 67%, and the results of the paired sample t-test for the experimental group show a significance value of 0.000<0.05, and The control group showed a significance value of 0.002<0.05, it can be concluded that Ha was accepted and Ho was rejected, so it can be concluded that group counseling with the REBT approach or group counseling is equally effective in increasing self-awareness and education, but there are differences in the level of effectiveness between group counseling and the group counseling approach. REBT and group counseling.